PENGEMBANGAN MICROLEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IX SMP NEGERI 4 BONTORAMBA - Matswana Amin; Nurhikmah H; Merrisa Monoarfa (LPPM Universitas Cipta Mandiri, 2025)
This development aims to Identify needs, Design and Measure the level of validity and Practicality of Microlearning in Science Subjects for Class IX of SMP Negeri 4 Bontoramba. This study refers to the steps of the Four-D development model developed by Thiragarajan consisting of several stages, namely Define, Design, Develop, Disseminate. The study was conducted at SMP Negeri 4 Bontoramba with a total of 23 students and 1 science subject teacher as research subjects. Based on the assessment of material experts and media experts, the average score for the material aspect was 97% (Very Good), the media aspect was 96% (very good). Based on student responses to the development test, it showed that the average small group trial was 93% (very practical), the large group trial was 94% (Very Practical), and the response from science subject teachers was 98% (very practical). This development resulted in Learning Media products in the form of Learning Animation Videos and Gamification based on Microlearning at SMP Negeri 4 Bontoramba.